A Difference-In-Difference Approach to Estimate the Price Effect of Market Entry in High-Speed Rail. Issue 3 (September 2022) - Beria, Paolo; Tolentino, Samuel; Shtele, Evgeniia; Lunkar, Vardhman
The effect of competition on prices in the passenger transport sector can be difficult to estimate because of many influencing factors such as state regulation, demand, seasonality, and reactions of indirect competitors. A case of great interest in the rail sector is Italy, where on-track competition in the high-speed segment has been in place for nearly ten years. The paper aims at answering the question whether—and how much—incumbent's prices are affected when competition starts on a route previously in monopoly. The case is the start of operations on the Turin–Milan–Venice route, where Italo entered in May 2018. Adopting a difference-in-difference approach, we check if Trenitalia changed the price strategy on the route before and after the entry, with respect to two control groups. The addition of placebo tests allows us to understand the ranges of significance of the results and to estimate the noise level of the estimates. Our findings suggest that the start of competition led to lower prices in the short-medium period. In the specific case, the Milano–Venezia route saw Trenitalia's prices reduced by 21–26% (±2–5%) in a time span of 84–140 days after Italo's entry and for advanced bookings from 2 to 10 days. Last-day prices remain unchanged, while early bookings are reduced by just 9%. This price reduction does not remain stable in the longer term, when other effects add up and blur the effect of the entry. Nevertheless, we keep observing a smaller, ∼15%, but still negative prices change.